2003
DOI: 10.1046/j.1469-0691.2003.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific seroprevalence of Human Herpesvirus 8 in Mediterranean regions

Abstract: The data suggest that HHV8 is widespread in the Mediterranean area, including regions like Albania that have not been previously investigated. The statistically significant association between HHV8 seropositivitity and increasing age suggests that non-sexual transmission routes may be involved in the spread of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 31 publications
(52 reference statements)
9
37
0
7
Order By: Relevance
“…The results also revealed an excess for persons born in two adjacent provinces in the northern region of Lombardy, which is consistent with the increased incidence of CKS and high HHV8 seroprevalence in another adjacent province (Ascoli et al, 2001;Tanzi et al, 2005). These provinces are located in the Po Valley, which, together with Sardinia, Sicily, and Puglia, has shown evidence of a higher incidence of CKS and seroprevalence of HHV8, compared with other areas in Italy (Lospalluti et al, 1995;Calabro et al, 1998;Whitby et al, 2000;Cattani et al, 2003). This could be related to environmental risks, including having been born in areas with endemic malaria (Geddes et al, 1995) and exposure to bloodsucking insects (Coluzzi et al, 2002;Ascoli et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results also revealed an excess for persons born in two adjacent provinces in the northern region of Lombardy, which is consistent with the increased incidence of CKS and high HHV8 seroprevalence in another adjacent province (Ascoli et al, 2001;Tanzi et al, 2005). These provinces are located in the Po Valley, which, together with Sardinia, Sicily, and Puglia, has shown evidence of a higher incidence of CKS and seroprevalence of HHV8, compared with other areas in Italy (Lospalluti et al, 1995;Calabro et al, 1998;Whitby et al, 2000;Cattani et al, 2003). This could be related to environmental risks, including having been born in areas with endemic malaria (Geddes et al, 1995) and exposure to bloodsucking insects (Coluzzi et al, 2002;Ascoli et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…Given that the area of birth is an important determinant because HHV8 is mostly acquired during childhood (Whitby et al, 2000;Cattani et al, 2003), we also calculated the SMRs for the region of birth (not recorded on the multiple-causes-of-death records), by linking the multiple-causes-of-death records with the National Mortality Database, using the individual anonymous six-digit identification code adopted for both databases. However, as the region of birth has been recorded in the National Mortality Database only since 1998, this linkage was only possible for 679 persons.…”
Section: Geographical Distribution Of Deceased Persons With Cksmentioning
confidence: 99%
“…The application of different serologic assays makes it difficult to compare directly the prevalence of HHV-8 antibodies in different populations [Rabkin et al, 1998]. Still, this study suggests that HHV-8 is prevalent in Greece, in the range observed in other Mediterranean countries [Calabro et al, 1998;Iscovich et al, 2000;Perna et al, 2000;Gambus et al, 2001;Cattani et al, 2003]. In particular, HHV-8 seroprevalence in the J. Med.…”
Section: Discussionmentioning
confidence: 86%
“…Virol. DOI 10.1002/jmv general population from Western Sicily is reported to be 11.5% , whereas the corresponding estimate for healthy individuals from Sardinia, Central-Southern Italy, and Albania is reported to be higher (25.0%, 18.3%, and 20.0%, respectively) [Cattani et al, 2003;Schinaia et al, 2004]. The prevalence of HHV-8 antibodies observed in the current study is in accordance with the seroprevalence rates reported in healthy adults from Israel (6.1%, 95% CI: 2.0, 10.1) [Iscovich et al, 2000] and in Spanish blood donors (6.5%, 95% CI: 4.6, 8.5) [Gambus et al, 2001].…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 95% of KS lesions show polymerase chain reaction (PCR) evidence of HHV8 infection [1]. KS is classically seen as a complication of HIV infection and in older men of Mediterranean, Central and Eastern European heritage [2]. However, iatrogenic KS can also occur in patients undergoing immunosuppressive therapies for autoimmune disorders and in patients who are transplant recipients [1].…”
Section: Letter To the Editormentioning
confidence: 99%